Spectrophotometric Methods for the Assay of Fluvoxamine Using Chromogenic Reagents - V. Annapurna; G. Jyothi; V. Nagalakshmi; B. B. V. Sailaja (E-Journal of Chemistry)
Simple, accurate and reproducible UV-Visible spectrophotometric methods were established for the assay of FXA based on the oxidative coupling and condensation reactions. Condensation and coupling of the FXA with Ninhydrin-Ascorbic acid is proposed in method A. Method B includes complexation of FXA with cobalt thiocyanate. The ligating property of FXA with sodium nitro prusside is incorporated in method C. The optical characteristics such as Beers law limits, molar absorptivity and Sandell’s sensitivity for the methods (A-C) are given. Regression analysis using the method of least squares was made to evaluate the slope(b), intercept(a) and correlation coefficient (r) and standard error of estimation (Se) for each system. Determination of FXA in bulk form and in pharmaceutical formulations were also incorporated.